UNI EROPA DAN DEMOKRATISASI DI KAWASAN BALKAN BARAT - Alfredha Shinta Putri; Ali Muhammad (Jurusan Ilmu Hubungan Internasional, 2017)
This article explores the role of the European Union in promoting democatisation of the countries in the Western Balkan, i.e, the former Yugoslavian states of Bosnia-Herzegovina, Croatia, Kosovo, Macedonia, Montenegro, and Serbia. After the end of the Cold War and the dissolution of Yugoslavia, these emerging countries underwent political transition toward democracy and aspire to join the EU. As international actors, the EU support the transition into a free-market economic system and strengthen democratic institutions in the region using various economic and political intruments. This study uses secondary data, such as, books, journals, articles, and relevant internet sites.